2009
DOI: 10.1016/j.gde.2009.08.004
|View full text |Cite
|
Sign up to set email alerts
|

New horizons at the caudal embryos: coordinated urogenital/reproductive organ formation by growth factor signaling

Abstract: SummaryThe cloaca/urogenital sinus and its adjacent region differentiate into the urogenital/reproductive organs. Caudal regression syndrome (CRS; including Mermaid syndrome), a type of severe cloacal malformation displays hindlimb fusion and urogenital organ defects, thus suggesting that such defects are caused by several morphogenetic alterations during early development. The attenuation of Bone Morphogenetic Protein (Bmp) signaling at the posterior primitive streak of embryos leads to the caudal dysmorphoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 66 publications
1
17
0
Order By: Relevance
“…However, the possibility remains that an imperforate anus induced by elevated RA may be homologous in amphioxus and vertebrates in the sense that RA signaling is transmitted via comparable gene networks to elicit similar changes in downstream effector genes determining cell morphology and adhesion. Developmental genetic studies in vertebrates have indicated some genes that are key components in directing hindgut morphogenesis (Ramalho‐Santos et al ; Nakata et al ; Suzuki et al ). For example in the mouse, when RA is elevated prior to opening of the anus, there is downregulation of Shh and BMP4 , genes required for anus formation and normally expressed in the cloacal epithelium and underlying mesenchyme, respectively (Sasaki et al ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the possibility remains that an imperforate anus induced by elevated RA may be homologous in amphioxus and vertebrates in the sense that RA signaling is transmitted via comparable gene networks to elicit similar changes in downstream effector genes determining cell morphology and adhesion. Developmental genetic studies in vertebrates have indicated some genes that are key components in directing hindgut morphogenesis (Ramalho‐Santos et al ; Nakata et al ; Suzuki et al ). For example in the mouse, when RA is elevated prior to opening of the anus, there is downregulation of Shh and BMP4 , genes required for anus formation and normally expressed in the cloacal epithelium and underlying mesenchyme, respectively (Sasaki et al ).…”
Section: Discussionmentioning
confidence: 99%
“…While the cells of the vertebrate limb bud arise through an epithelial-to-mesenchymal transition (EMT) of an epithelial lateral plate mesoderm (LPM) population lining the coelomic cavity 11 , the developmental origin of external genitalia in vertebrates is still unclear. We developed a lenti-viral lineage tracing approach (see Methods), to systematically follow the two sources previously proposed, the LPM and tail bud 10 , 12 , 13 , in three amniote species, mouse, chicken and anole. Injections into the coelom of embryonic day 9.5 (E9.5) mouse embryos label cells surrounding the coelom as well as the developing hindlimb ( Fig.…”
mentioning
confidence: 99%
“…These findings indicate the existence of developmental programs for the coordinated organogenesis of urogenital/reproductive tissues based on growth factor function and crosstalk. [6] Interestingly, structures that are developmentally separate from these caudal elements such as the brain, proximal spine and spinal cord, are generally spared by CRS. The consequences of the disruption after the maturation of spinal cord's caudal portion ensue after the 4 th week of gestation are different.…”
Section: Discussionmentioning
confidence: 99%